Intra-abdominal Migration of a Uterine Device - Yazough, Issam; Hachim, Hajar (Integrative Journal of Medical Sciences, 2024)
The intrauterine device (IUD) is one of the most commonly used contraceptive methods in the world. However, this method can be associated with complications, including uterine perforation with secondary migration into the abdominal cavity. Intra-abdominal migration of the IUD is a rare but serious complication. We report a clinical case of intra-abdominal migration of an IUD in a 39-year-old woman with no significant medical history, which required laparoscopic diagnosis and treatment.